2009
DOI: 10.1007/s00595-008-3862-z
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-two metachronous multiple signet-ring cell carcinomas treated with repeated gastrectomies and repeated endoscopic mucosal resections: Report of a case

Abstract: A 45-year-old Japanese woman underwent an endoscopic mucosal resection (EMR) for early gastric cancer at the Cancer Institute Hospital in July 1996. The patient then underwent a distal gastrectomy in 2002 because of a new early gastric cancer and repeated EMR for a total of six early gastric cancers in 2007. Finally, a total gastrectomy was performed in February 2008. The pathological examination of the resected specimen indicated 14 synchronous multiple early gastric cancers. Although the incidence of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Apparently they were likely to be intramucosal, but there was a high incidence of metachronous multiple lesions. We considered the possibility of HDGC that we could not control multiple SRCCs by repeated ESD or distal gastrectomy similar to a previous report [11]. After the explanation about the risk for recurrence or metachronous lesions in any part of the stomach, next month, a total gastrectomy and Roux-en-Y reconstruction with D2 lymph node dissection were carried out as the patient wished.…”
Section: Case Reportmentioning
confidence: 98%
“…Apparently they were likely to be intramucosal, but there was a high incidence of metachronous multiple lesions. We considered the possibility of HDGC that we could not control multiple SRCCs by repeated ESD or distal gastrectomy similar to a previous report [11]. After the explanation about the risk for recurrence or metachronous lesions in any part of the stomach, next month, a total gastrectomy and Roux-en-Y reconstruction with D2 lymph node dissection were carried out as the patient wished.…”
Section: Case Reportmentioning
confidence: 98%
“…[4][5][6][7][8] Kosaka et al 7 reported that the incidence of multiple gastric cancers was 60% in the differentiated-plus-differentiated type, 24% in the differentiated-plus-undifferentiated type, and 16% in the undifferentiated-plus-undifferentiated type, whereas it was 53% in early-plus-early gastric cancer, 16% in earlyplus-advanced gastric cancer, and 31% in advanced-plusadvanced gastric cancer. The incidence of four separate gastric cancers was reported to be very rare (0.24%).…”
Section: Discussionmentioning
confidence: 94%
“…The present case belongs to the "differentiated-plus-undifferentiated type" and the "early-plus-advanced gastric cancer type," and involves four separate gastric cancers, making it extremely unusual. 8 Kitamura et al 9 tried to explain why the incidence of multifocal lesions is higher in early gastric cancer than in advanced gastric cancer by referring to the theory of collision cancer, which suggests that two different early synchronous lesions may fuse together after lateral and vertical growth, becoming a single advanced cancer. Meanwhile, multiple gastric cancers often showed similarities in their macroscopic and microscopic morphology, which suggests a similar pathway of tumor development.…”
Section: Discussionmentioning
confidence: 98%
“…Diagnosis and treatment using interventional endoscopy are now performed as a routine modality in clinical practice. [3][4][5] In parallel with the gradual development of interventional endoscopy, there have been growing demands for less invasive surgical procedures. Since the initial laparoscopic cholecystectomy was performed by Mouret in 1987, 6 endoscopic surgery, in which surgical procedures are performed within a body cavity under laparoscopy/ thoracoscopy, has become globally recognized as a minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%